The Wrath of Capital: Neoliberalism and Climate Change Politics – Reflections. (June 2015) - Parr, Adrian
Abstract: In this article the author responds to the criticism that The Wrath of Capital: Neoliberalism and Climate Change Politics does not provide solutions to problems the book identifies. The author argues for the importance of developing a deep understanding of how neoliberalism has become the standard against which all social, economic, cultural, and political responses to climate change are measured. She goes onto re-iterate the main thesis of The Wrath of Capital, namely that this does not constitute an effective or equitable response to the challenges climate change presents. In her view understanding and thinking are important ingredients in developing a sustainable and equitable solution to climate change.